The effects of structural integrity of graphene on the thermoelectric properties of the n-type bismuth-telluride alloy - Farah M. El-Makaty (14157090) (2021)
This study examines the effects of the structural integrity of graphene on the thermoelectric properties of n-type bismuth telluride alloy. Graphene/Bi2Te2.7Se0.3 composites were prepared via mechanical alloying and spark plasma sintering techniques. Different graphene concentrations (0.05 and 0.5 wt%) and addition times (20 hrs, 10 mins, and 1 min) were considered. The thermoelectric properties were measured, and the results showed that the milling time affects graphene structure as well as its agglomeration. It is revealed that the optimum time to add the two-dimensional filler is during the last phase of mechanical milling as it will preserve graphene’s structure and boost the electrical conductivity. It is also shown that as the milling time of graphene increases, the Seebeck coefficient improves. Even though an increase in the thermal conductivity is expected due to the high electrical conductivity, a clear reduction in the lattice thermal conductivity part was obtained due to the increased scattering at the new interfaces. The figure-of-merit for the optimum sample with 0.05 wt% graphene added in the last 10 mins of milling had an improvement of 19% at room temperature reaching a value of 0.5, and 25% at 160 °C achieving a final value of 0.81. Other Information Published in: Journal of Alloys and Compounds License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jallcom.2021.160198